Treatment of acute renal failure in Germany : Analysis of current practice - Schmitz, M.; Heering, P. J.; Hutagalung, R.; Schindler, R.; Quintel, M. I.; Brunkhorst, F. M.; John, Stefan; Joerres, A. (Medizinische Klinik - Intensivmedizin und Notfallmedizin, 2015)
There are currently no reliable data on the differential use of renal replacement therapy (RRT) options for critically ill patients with acute renal failure in Germany.A questionnaire-based survey was delivered to 2265 German intensive care units. The questionnaire contained 19 questions regarding RRT.A total of 423 German intensive care units participated in the survey. The offered modalities of RRT varied significantly: the smaller the facility, the fewer different RRT options were available. Intermittent dialysis procedures were available in only 35 % of hospitals with up to 400 beds. In university hospitals, hemodynamically unstable patients were exclusively treated by continuous RRT, whereas in hospitals with up to 400 beds, intermittent RRT was also used. In addition, treatment practice was also dependent on the specialization of the treating physicians: Isolated acute renal failure was treated more often intermittently by nephrologists compared to anesthesiologists (79.7 vs. 43.3 %). Nephrologists also used extracorporeal RRT more often in cardiorenal syndrome (54.3 vs. 35.8 %), whereas anesthesiologists preferred them in sepsis (37.3 vs. 23.1 %). The choice of anticoagulant varied as well: Hospitals with up to 400 beds offered regional citrate anticoagulation in only 50 % compared to 90 % of university hospitals.Currently, RRT treatment in acute renal failure on German intensive care units seems to be dependent on the size, local structures, and education of the intensivists rather than patient needs. Our results demonstrate the necessity to establish cross-disciplinary standards for the treatment of acute renal failure in German intensive care units.
EVALuna2:3758